Mitogen-activated protein kinase phosphatase 1 protects PC12 cells from amyloid beta-induced neurotoxicity - Gu, Yue (Neural Regen Res, 2018)
The mitogen-activated protein kinase (MAPK) signaling pathway plays an important role in the regulation of cell growth, proliferation, differentiation, transformation and death. Mitogen-activated protein kinase phosphatase 1 (MKP1) has an inhibitory effect on the p38MAPK and JNK pathways, but it is unknown whether it plays a role in Aβ-induced oxidative stress and neuronal inflammation. In this study, PC12 cells were infected with MKP1 shRNA, MKP1 lentivirus or control lentivirus for 12 hours, and then treated with 0.1, 1, 10 or 100 μM amyloid beta 42 (Aβ(42)). The cell survival rate was measured using the cell counting kit-8 assay. MKP1, tumor necrosis factor-alpha (TNF-α) and interleukin-1β (IL-1β) mRNA expression levels were analyzed using quantitative real time-polymerase chain reaction. MKP1 and phospho-c-Jun N-terminal kinase (JNK) expression levels were assessed using western blot assay. Reactive oxygen species (ROS) levels were detected using 2′,7′-dichlorofluorescein diacetate. Mitochondrial membrane potential was measured using flow cytometry. Superoxide dismutase activity and malondialdehyde levels were evaluated using the colorimetric method. Lactate dehydrogenase activity was measured using a microplate reader. Caspase-3 expression levels were assessed by enzyme-linked immunosorbent assay. Apoptosis was evaluated using the terminal deoxynucleotidyl transferase dUTP nick end labeling method. MKP1 overexpression inhibited Aβ-induced JNK phosphorylation and the increase in ROS levels. It also suppressed the Aβ-induced increase in TNF-α and IL-1β levels as well as apoptosis in PC12 cells. In contrast, MKP1 knockdown by RNA interference aggravated Aβ-induced oxidative stress, inflammation and cell damage in PC12 cells. Furthermore, the JNK-specific inhibitor SP600125 abolished this effect of MKP1 knockdown on Aβ-induced neurotoxicity. Collectively, these results show that MKP1 mitigates Aβ-induced apoptosis, oxidative stress and neuroinflammation by inhibiting the JNK signaling pathway, thereby playing a neuroprotective role.